2023
DOI: 10.15243/jdmlm.2023.111.5037
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of slow-release fertilizer with coconut shell biochar and activated natural zeolite for red onion (Allium ascalonium)

Edwin Permana,
Kiranti Aulia,
Herman Aziz
et al.

Abstract: <p>Using fertilizers is one of the efforts to increase crop productivity, but conventional fertilizers tend to be easily leached so it becomes ineffective. Slow-release fertilizer (SRF) is a modified fertilizer that releases nutrients slowly or gradually so that the use of fertilizer becomes more effective. SRF can be synthesized by mixing fertilizers with zeolite as a slow-release agent. Because natural zeolite contains many impurities that cover the pores of the zeolite, it is necessary to carry out an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Beyond biochar, various other organic amendments have been shown to positively impact onion root length. Studies demonstrated that wheat straw, coconut shell, phragmites, sawdust, cotton sticks, and poultry litter biochars all significantly increased root length in tested onion cultivars, with some reaching up to 25.21 cm [38,52,53]. According to the literature, it is suggested that biochar, fertilizers containing sulfur, and various organic amendments can significantly promote onion growth by increasing plant height and root length.…”
Section: Functional Traitsmentioning
confidence: 99%
“…Beyond biochar, various other organic amendments have been shown to positively impact onion root length. Studies demonstrated that wheat straw, coconut shell, phragmites, sawdust, cotton sticks, and poultry litter biochars all significantly increased root length in tested onion cultivars, with some reaching up to 25.21 cm [38,52,53]. According to the literature, it is suggested that biochar, fertilizers containing sulfur, and various organic amendments can significantly promote onion growth by increasing plant height and root length.…”
Section: Functional Traitsmentioning
confidence: 99%